2002
DOI: 10.1016/s0735-1097(02)01895-8
|View full text |Cite
|
Sign up to set email alerts
|

long-term clinical effect of hemodynamically optimized cardiac resynchronization therapy in patients with heart failure and ventricular conduction delay

Abstract: Cardiac resynchronization therapy produces a long-term improvement in the clinical symptoms of patients with HF who have a ventricular conduction delay. The differences between optimized biventricular and univentricular therapy appear to be small for short-term treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
483
0
28

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 891 publications
(539 citation statements)
references
References 26 publications
23
483
0
28
Order By: Relevance
“…CRT improves left ventricular (LV) function, increases exercise capacity, improves heart failure symptoms, and reduces hospitalizations and mortality (1)(2)(3)(4)(5)(6). Patients are chosen for CRT based on the presence of a prolonged QRS interval (Ͼ120 msec) on a surface electrocardiogram (2,3,6,7). Prolonged QRS duration has been used as an index of dyssynchrony, with a longer QRS interval corresponding to a greater degree of dyssynchrony (8).…”
mentioning
confidence: 99%
“…CRT improves left ventricular (LV) function, increases exercise capacity, improves heart failure symptoms, and reduces hospitalizations and mortality (1)(2)(3)(4)(5)(6). Patients are chosen for CRT based on the presence of a prolonged QRS interval (Ͼ120 msec) on a surface electrocardiogram (2,3,6,7). Prolonged QRS duration has been used as an index of dyssynchrony, with a longer QRS interval corresponding to a greater degree of dyssynchrony (8).…”
mentioning
confidence: 99%
“…[1][2][3] CRT improves left ventricular systolic and diastolic function 4 and clinical status 5 and reduces functional mitral regurgitation (MR). 6 Whether CRT significantly affects exercise-induced changes in MR has never been investigated.…”
mentioning
confidence: 99%
“…Despite this lack of approval, information from recent clinical trials have consistently suggested the widespread use of nitrates in the treatment of patients with CHF. [3][4][5] The purpose of the present study was to evaluate the attitudes of physician members of the Heart Failure Society of America regarding the use of nitrates in the management of chronic CHF in the United States.…”
mentioning
confidence: 99%
“…On the clinical side, several trials have documented both increased functional capacity, as evaluated by means of the 6-minute walking test and the VO2 peak, and improvements in quality of life and New York Heart Association (NYHA) class [15][16][17][18][19][20][21][22][23]. Moreover, CRT has been seen to reduce HF hospitalizations and mortality by 36% [22], and the total number of days of hospitalization by 77% [17].…”
Section: Resultsmentioning
confidence: 99%